Catalan cabalist Ezra of Gerona on the Song of Songs - Moreno-Szypowska, Jadwiga Clea (Filozofia Chrześcijańska, 2024)
The Catalan Kabbalist Ezra of Gerona (c.1175–1245) places within his exegesis of the Song of Songs a commentary on the Book of Job, more specifically on its 28th chapter known as the Hymn of Wisdom, thus connecting the most mystical work of Scripture with the most philosophical. In this way, he is able to convey to his disciples – for they were the recipients of his work – the cosmogonic vision of the world contained in the tree of the sefirot, which allows him to indirectly link the Song of Songs to the Act of Creation. According to the Kabbalistic interpretation, the lower world emerged from the second sephira or Wisdom (Chochmah) and in its first form was identical to the higher one. It was not until the fall of man that the lower world diverged from its original and the universal aim became to reconnect it to the higher one in every respect: cosmic, national and individual. In Ezra of Gerona’s interpretation, the Bride of the Song of Songs is at the same time the Universe, the Community of Israel and the soul of the believer, all moving towards a loving union with the Beloved, which is possible because every form of existence is called to perfection. The Jews, in any case, are convinced that if man has contributed to the ‘corruption’ of creation, he too can, through his actions, restore perfection to the world. In line with this conviction, the Song of Songs, in addition to its cosmogonic message, also contains a didactic and moral injunction, which Ezra of Gerona presents to his adepts.